The Influence of the Initial Density of Metastable States and Electron Density on the Pulse Repetition Rate in a Copper-Vapor Laser; Laser Physics; Vol. 11, No. 5 - Boichenko A. M.; Evtushenko G. S. Gennady Sergeevich; Yakovlenko S. I.; Zhdaneev O. V. Oleg Valeryevich (2001, 2001)
Title screen